BELIEF AND EVIDENCE, AND HOW IT MAY AID REFLECTION CONCERNING CHARLIE HEBDO. Issue 42 (9th December 2015) - Watson, Brenda
Abstract : Starting from support for James's critique of Clifford's dictum, the article argues for holding beliefs, whether secular or religious, firmly but provisionally, remaining open to fresh experience. This consideration prompts reflection on the debate following the attack on Charlie Hebdo. Alternative beliefs were opposing each other with seemingly equal certainty. The justification for insistence on the right to free speech itself requires scrutiny. The article finishes by noting the baleful effects of the intellectual apartheid which has tended to be practised in the West which presumes that religion and reason have nothing to do with each other.